Simulation of temperature during vacuum microwave drying of mixed potato and apple slices - Huang, Luelue; Chen, Huizhi; Zhang, Min; Liu, Wenchao; Mujumdar, Arun S.; Yu, Dongxing (Drying technology, 2022)
The increased use of vacuum microwave drying in food industry is attributed to shorter drying time and lower temperature. The temperature change of materials is difficult to model due to the vacuum condition. A simplified mathematical model is presented subject to some assumptions to predict the temperature distribution in slices made using a mixture of potato and apple purées. Dielectric loss factors of mixed slices were found to increase with temperature and water content. The model accounts for temperature and moisture-dependent dielectric loss factor which yields a useful predictive tool.